Correlation of vertical dimension with lip position, nasolabial angle and incisal display at rest and at smile in young adults - Badusha S, Jahamgeer; Joneja, Purva; Agarwal, Anshu; Singh Choudhary, Deepak (Orthodontic Journal of Nepal, 2021)
Introduction: Photography has been given a great importance in diagnosis in orthodontics, the study of certain aesthic parameter on digitilzed photographs can provide an additional diagnostic tool. This study is designed to compare facial parameters and various photographic parameters among patients with long, average, short faces in central Indian population. Also an alternative method to cephalometric analysis needs to be worked upon which is reliable, easily assessable and convenient for multiple usage by the orthodontist to direct his/her treatment. Materials and Methods: 150 subjects (75 males and 75 females) selected and examined by two methods clinical examination and photographic examination by using ImageJ software. Results: The results of this study shows there is significant correlation between vertical dimension, incisal display upper lip length, lower lip length and nasolabial angle and there is no significant difference between clinical examination and photographic examination done with Image J software. Conclusion: This study concluded that the vertical proportions of facial soft tissue follow the underlying vertical skeletal pattern, high vertical dimension is associated with short upper lip, more incisal display and high clinical FMA. The low vertical dimension is associated with acute nasolabial angle and low clinical FMA. Photogrammetry was found to be a quick easy, cost effective and reliable diagnostic tool which can reduce radiation exposure and reduce the number of cephalograms during treatment